Fall of Newspapers’ Sports Coverage during Corona Pandemic in Bangladesh: An Empirical Study - Haider, Shaonti; Joy, Tonmoy Saha (Social Science Review, 2024)
In this study, we have tried to analyse how the newspapers dealt with the pandemic situation. Due to COVID-19, sports events (both international and national levels) were stopped for a long time. In those days, it was a challenge for the daily newspapers to continue sports pages with regular trends. The policies and new trends that have been taken by the national dailies to cope with this situation have been analysed here. To conduct the research, we used the content analysis method. In this research, we have observed a significant decline in the number of news items and news areas on the sports pages. Cricket and football were the main sources of news, and most of the news items were male-centred. During the pandemic, using colours in headlines decreased. The Prothom Alo experienced a scarcity of advertisements though The Daily Observer did not experience it. The trend of using photos (with news) increased a little during the pandemic. Overall, many challenges were faced during this period by the newspaper industry, especially by the sports desk. Social Science Review, Vol. 40(2), December 2023 Page: 23-38